KINERJA BIOREAKTUR HIBRID ANAEROB MEDIA BATU DENGAN RESIRKULASI UNTUK MENGOLAH AIR BUANGAN ORGANIK KONSENTRASI TINGGI - HANDAJANI (NIM 25397009), MARISA
Abstract : Anaerobic hybrid bioreactor is a combination of an up-flow anaerobic sludge blanket as suspended growth system, with an anaerobic filter as with attached growth system. In this research, stone is used as the microorganism attachment media. The feeding solution is made from molasses, which is diluted to make an artificial high organic content wastewater. The hydraulic residence time (HRT) for degradation process is 30 hours and the height ratio is 0.5. The organic concentration is varied from 10.000 to 40.000 mg COD/L. The recirculation factor is also varied from 0% to 100% while the organic concentration is kept constant around 10.000 mg COD/L. The process in the bioreactor is still dominated by the acidogenous process in both suspended and attached growth systems. The methanogenous has already started, even though it has not completed yet. For organic content around 10.000 to 40.000 mg/L the growth yield is 0.704 mg VSS/mg COD removed. The total fatty acid production is evolved between 0.092 to 1.244 mg fatty acid/mg COD removed. The methane gas production yield is about 0,0017 to 0,0024 L CH4/g COD removed. The organic concentration and recirculation are not the determination factors in degrading organic wastewater using anaerobic hybrid bioreactor with stone media and height ratio 0.5.